THE UNITY OF UMMAH THROUGH PURIFICATION OF SOUL (TAZKIYYAH AL-NAFS) IN AL-QURAN - Muhammad Khairi Mahyuddin (Jurnal Ushuluddin Adab dan Dakwah, 2019)
The unity of ummah has been mentioned many times in al-Quran. It is pivotal in Islam as a fundamental strength to develop and manage Muslim community in a country to a betterment of life in this world and hereafter. However, the existence of the different opinions and methodologies that lead to the establishment of various school of thoughts are inescapable due to ordinary internal and external factors that emerged. Such different phenomenon creates worse and chaos if the ethics of disagreement have been disappeared from the true purification of soul. In fact, al-Quran mentions many times the importance of purification of soul as the central of goodness, virtues and solidarity. This practice was exercised seriously by the Prophet and his companions as well as their followers until they were well recognized as the most excellent ummah in their era. This discourse uses historical and content analysis study to explain the relationship between the purification of soul with the unity of ummah. Finally, the unity of ummah is possible to be achieved through purification of soul as urged in al-Quran by sharing a similar ultimate purpose of life, responsibility and behaving with the praiseworthy qualities based on tawhid orientation.